2016
DOI: 10.4236/eng.2016.810060
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Large Sized Compacted Baked Clay Blocks as a Walling Material

Abstract: Some disadvantages associated with conventional brick masonry are: high cost of construction, lower compressive strength and less durability. In order to resolve these problems, a new technique of constructing walls using large size baked clay blocks is introduced. For this purpose, clay blocks of size 150 mm × 300 mm × 1980 mm were cast at a pressure of 6 MPa, and fired at a temperature of 700˚C. In this paper, compressive strength and tensile strength of baked clay were investigated in order to find its suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Previous conducted studies reported that baked clay exhibited 1.5 to 2 times higher crushing strength than that of normal concrete [7][8][9][10][11][12][13][14][15]. RBC beams with tensile reinforcement, without shear and compressive reinforcement, only failed at the ultimate load of 80 kN applied at mid span [15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous conducted studies reported that baked clay exhibited 1.5 to 2 times higher crushing strength than that of normal concrete [7][8][9][10][11][12][13][14][15]. RBC beams with tensile reinforcement, without shear and compressive reinforcement, only failed at the ultimate load of 80 kN applied at mid span [15].…”
Section: Introductionmentioning
confidence: 99%